Phosphatidic acid produced by phospholipase Dα1 and Dδ is incorporated into the internal membranes but not involved in the gene expression of RD29A in the abscisic acid signaling network in Arabidopsis thaliana - Ndathe, Ruth; Kato, Naohiro (Frontiers in Plant Science, 2024)
Core protein components of the abscisic acid (ABA) signaling network, pyrabactin resistance (PYR), protein phosphatases 2C (PP2C), and SNF1-related protein kinase 2 (SnRK2) are involved in the regulation of stomatal closure and gene expression downstream responses in Arabidopsis thaliana. Phosphatidic acid (PA) produced by the phospholipases Da1 and Dd (PLDs) in the plasma membrane has been identified as a necessary molecule in ABA-inducible stomatal closure. On the other hand, the involvement of PA in ABA-inducible gene expression has been suggested but remains a question. In this study, the involvement of PA in the ABA-inducible gene expression was examined in the model plant Arabidopsis thaliana and the canonical RD29A ABAinducible gene that possesses a single ABA-responsive element (ABRE) in the promoter. The promoter activity and accumulation of the RD29A mRNA during ABA exposure to the plants were analyzed under conditions in which the production of PA by PLDs is abrogated through chemical and genetic modification. Changes in the subcellular localization of PA during the signal transduction were analyzed with confocal microscopy. The results obtained in this study suggest that inhibition of PA production by the PLDs does not affect the promoter activity of RD29A. PA produced by the PLDs and exogenously added PA in the plasma membrane are effectively incorporated into internal membranes to transduce the signal. However, exogenously added PA induces stomatal closure but not RD29A expression. This is because PA produced by the PLDs most likely inhibits the activity of not all but only the selected PP2C family members, the negative regulators of the RD29A promoter. This finding underscores the necessity for experimental verifications to adapt previous knowledge into a signaling network model before its construction.